Echocardiography, lung ultrasound, and cardiac magnetic resonance findings in COVID‐19: A systematic review. Issue 8 (8th July 2021) - Barssoum, Kirolos; Victor, Varun; Salem, Ahmad; Kumar, Ashish; Mubasher, Mahmood; Hassib, Mohab; Magdi, Mohamed; Renjithlal, Sarathlal; Abdelazeem, Mohamed; Shariff, Mariam; Idemudia, Osarenren; Ibrahim, Mounir; et al.
Abstract: Background: The manifestations of COVID‐19 as outlined by imaging modalities such as echocardiography, lung ultrasound (LUS), and cardiac magnetic resonance (CMR) imaging are not fully described. Methods: We conducted a systematic review of the current literature and included studies that described cardiovascular manifestations of COVID‐19 using echocardiography, CMR, and pulmonary manifestations using LUS. We queried PubMed, EMBASE, and Web of Science for relevant articles. Original studies and case series were included. Results: This review describes the most common abnormalities encountered on echocardiography, LUS, and CMR in patients infected with COVID‐19.